Case Series on Applications of EMDR to OCD - Woo, Matthew (Advances in Social Sciences Research Journal, 2021)
This paper is an attempt to draw a parallel between the exposure and response prevention (ERP) procedures in CBT (cognitive behaviour therapy) and the desensitisation procedures in EMDR (eye movement desensitisation processing). This paper also suggests an alternative targeting sequence that follows from the standard EMDR protocol to draw upon the strengths and application of ERP procedures in the treatment of OCD (obsessive compulsive disorder).